Energy Harvesting from Pressure Fluctuations in Water Pipelines Using PZT4 and PZT5 Ceramic Piezoelectrics - Uyar, Muhammed Mustafa; Çıtlak, Aydın; Vural, Hakan (Fırat University, 2026)
With the expansion of global energy consumption and the increasing reliance on fossil fuels, the costs of these fuels are also rising, and the search for alternative energy sources is accelerating. The conversion of non-structural mechanical energy into electrical energy, the primary target of our study, is gaining importance every day. Piezoelectric properties can generate voltage under mechanical stress, and with these effects, energy recovery applications create active potential. This research investigates whether sudden pressure fluctuations in water prices can be used as a mechanical source for piezoelectric energy harvesting. For the experimental study, an experimental setup consisting of 1-inch diameter pipes, similar to municipal water lines, was constructed. A PZT-4 type piezoelectric material was placed inside the pipe. It was electrically insulated to ensure safe use since it would come into contact with water. Ball valves were chosen to ensure controlled pressure cycles in the experimental setup. Pressure regulators were used to maintain consistent system pressure and prevent exceeding limits. The pressure ranges in which the experiments were conducted were between 1 and 6 bar.Sudden pressure changes occurring in each cycle generated mechanical stress on the piezoelectric element, producing a measurable stress output. After conducting tests with PZT-4 material in the experimental setup, the same experiments were repeated with PZT-5 material. The data obtained from the experimental setup were analyzed, and the voltage values were used to determine the optimum working pressure range.Piezoelectric materials compatible with the results are available and suitable for integration into infrastructures. It was assessed that some of the lost hydraulic energy could be recovered in this way. Furthermore, it was concluded that it would contribute to sustainable energy applications.

Küresel enerji tüketiminin artması ve fosil yakıtlara olan bağımlılığın giderek artmasıyla birlikte, bu yakıtların maliyetleri de yükselmekte ve alternatif enerji kaynakları arayışı hızlanmaktadır. Çalışmamızın temel hedefi olan yapısal olmayan mekanik enerjinin elektrik enerjisine dönüştürülmesi her geçen gün daha da önem kazanmaktadır. Piezoelektrik özellikler, mekanik gerilim altında voltaj üretebilir ve bu etkilerle enerji geri kazanım uygulamaları aktif bir potansiyel yaratmaktadır. Bu araştırma, su hatlarındaki ani basınç dalgalanmalarının piezoelektrik enerji hasadı için mekanik bir kaynak olarak kullanılıp kullanılamayacağını incelemektedir. Deneysel çalışma için, belediye su hatlarına benzer 1 inç çapında borulardan oluşan bir deney düzeneği kurulmuştur. Borunun içine PZT-4 tipi bir piezoelektrik malzeme yerleştirilmiştir. Su ile temas edeceği için güvenli kullanım sağlamak amacıyla elektriksel olarak yalıtılmıştır. Deneysel düzende kontrollü basınç döngülerini sağlamak için küresel vanalar seçilmiştir. Sistem basıncının tutarlı kalmasını ve limitlerin aşılmasını önlemek için basınç regülatörleri kullanılmıştır. Deneylerin yapıldığı basınç aralıkları 1 ile 6 bar aralığında belirlenmiştir. Her döngüde meydana gelen ani basınç değişiklikleri, piezoelektrik eleman üzerinde mekanik gerilim oluşturarak ölçülebilir bir gerilim çıktısı üretmiştir. Deneysel düzende PZT-4 malzemesi ile yapılan testlerden sonra, aynı deneyler PZT-5 malzemesi ile tekrarlanmıştır. Deneysel düzenekten elde edilen veriler analiz edilmiş ve voltaj değerleri optimum çalışma basıncı aralığını belirlemek için kullanılmıştır. Sonuçlarla uyumlu piezoelektrik malzemeler mevcuttur ve altyapılara entegre edilmeye uygun olduğu görülmüştür. Bu şekilde kaybedilen hidrolik enerjinin bir kısmının geri kazanılabileceği değerlendirilmiştir. Ayrıca, bunun sürdürülebilir enerji uygulamalarına katkıda bulunacağı sonucuna varılmıştır.
PZT4 ve PZT5 Seramik Piezoelektrikler Kullanılarak Su Boru Hatlarındaki Basınç Dalgalanmalarından Enerji Elde Edilmesi
Keywords: Fluid Mechanics and Thermal Engineering (Other); Akışkan Mekaniği ve Termal Mühendislik (Diğer)